Studies on Lophocoleaceae XXII. The systematic position of Amphilophocolea RMSchust. together with comments on the status of Tetracymbaliella Grolle and Lamellocolea RMSchust - Engel, J. J.; He, X. L.; Glenny, D. (Phytotaxa, 2014)
DNA sequence results show that Amphilophocolea, a monotypic genus endemic to New Zealand, is nested within Heteroscyphus. A morphological examination of specimens that agree with the protologue shows it to be identical to Heteroscyphus knightii. Heteroscyphus cymbaliferus in the DNA sequence analyses is sister to the clade consisting of the rest of Heteroscyphus, and the monophyletic Chiloscyphus and Lamelocolea, and suggests that the genus Tetracymbaliella should be reinstated. Lamellocolea is not included in either Chiloscyphus or Heteroscyphus in the trees derived from sequence data, but its position as sister to Chiloscyphus obtained from the Bayesian analysis lacks significant support.